Fundamentální analýza vybraných českých akciových titulů - Veselík, Tomáš (Vysoké učení technické v Brně. Fakulta podnikatelská, 2009)
Tato diplomová práce se zaměřuje na praktické využití fundamentální analýzy akcií. Jejím cílem je zhodnotit na základě určených postupů společnosti ČEZ, a. s, ECM Real Estate Investments A. G., a poté rozhodnout o možnostech případných investic do těchto titulů. Práce je rozdělena do dvou částí. První část se zabývá teoretickými východisky řešení fundamentální analýzy a stručným popisem dalších dvou možných metod analýzy akciových titulů – grafickou a psychologickou analýzou. V druhé části práce najdeme praktické vypracování fundamentální analýzy pro výše zmíněné společnosti a na závěr shrnutí dosažených výsledků se stručným komentářem pro případné investory.

This master’s thesis is aimed at practical use of fundamental analysis of stocks. Its main goal is, on the basis of defined procedures, to analyze and valorize companies ČEZ, a. s., ECM Real Estate Investments A. G. and then decide about possible investments into the stocks of these companies. This thesis is divided into two main parts. First part deals with theoretical solutions of fundamental analysis and brief comment of another two ways how to analyze stocks – graphic and psychological analysis. In second part there is a practical elaboration of fundamental analysis for aforesaid companies and, in the end of this thesis, there is a summary of achieved results with brief commentary for possible investors.
Fundamental Analysis of Chosen Czech Stocks
Keywords: Fundamentální analýza; ECM Real Estate Investments A. G.; ČEZ; a. s.; akcie; Fundamental analysis; ECM Real Estate Investments A. G.; ČEZ; a. s.; a stock